KORELASI PENGUASAAN KOSAKATA DENGAN KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS X SMK NEGERI 2 PADANG - Frecelya, Adryani Fyola; Gani, Erizal (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT This study has three objectives as follows. First, it describes the level of vocabulary mastery of class X students of SMK Negeri 2 Padang. Second, describe the level of exposition text writing skills of class X students of SMK Negeri 2 Padang. Third, describe the correlation of vocabulary mastery with text writing skills of exposition students of class X SMK Negeri 2 Padang. This type of research is quantitative with descriptive methods. The design of this study is correlational. This study consisted of two variables, namely vocabulary mastery of class X vocational high school students 2 Padang and writing exposition text skills of class X students of vocational high school 2 Padang. The data of this study are the scores on the vocabulary mastery test results and the scores on the exposition text writing skills test results. Data is obtained through two types of tests, namely objective tests to measure vocabulary mastery and performance tests to measure exposition text writing skills. Based on the results of the analysis and discussion, three things are concluded as follows. First, the vocabulary mastery of grade X students of SMK Negeri 2 Padang is in a qualification More Than Enough (72.36). Second, the exposition writing skills of the X grade students of SMK Negeri 2 Padang are in Good qualification (78.68). Third, the mastery of vocabulary correlates with the writing skills of exposition text students of class X SMK Negeri 2 Padang. Thus, for exposition text writing skills, vocabulary mastery is needed.Â Kata Kunci: korelasi, penguasaan kosakata, keterampilan menulis teks eksposisi